The welfare effects of attracting foreign direct investment in the presence of unemployment - Yoshitomo Ogawa; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2016)
We develop a 222 model with the following features: (1) one sector is perfectly competitive while the other is oligopolistic; (2) one country has unemployment while the other attains full employment; (3) oligopolists move internationally; and (4) the ownership of each oligopolist is internationally shared. The welfare effects of various tax-cum-subsidies are examined. If the oligopolistic sector is capital intensive, subsidizing the oligopolists' profits, inflows, production or employment is more likely to harm the country. The number of domestically based oligopolists, the volume of domestic demand for the oligopoly-produced commodity, and the country's ownership share of oligopolists also influence the effect.
Keywords: F12; F13; H25; H71; R38; 330; Corporate Taxation; Production Subsidies; Unemployment; Oligopoly